2007
DOI: 10.1177/1065912907301682
|View full text |Cite
|
Sign up to set email alerts
|

A Woman's Work Is Never Done? Fund-Raising Perception and Effort among Female State Legislative Candidates

Abstract: The lack of female politicians has been attributed to a lack of female candidates for office. However, the reason why there are so few female candidates is not clear. The author examines whether differences in fund-raising perceptions and effort between female and male state legislative candidates contribute to the lack of female candidates. The results indicate that women do tend to be more concerned about fund-raising, as is evidenced by greater effort devoted to this campaign function as compared to their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…The belief that he or she can put together a donor network and raise the necessary funds to win will be crucial to a candidate's decision. The political ambition literature tells us that women are less likely to view themselves as qualified to run for office, and they are more likely to express concerns about fundraising (Fox and Lawless 2011;Fulton et al 2006;Jenkins 2007). Thus, more Democratic women than Republican women may run because the Democratic women see more potential avenues for fundraising, which helps them overcome this ambition deficit.…”
Section: Evaluating Gender and Partisan Differences In Fundraising: Amentioning
confidence: 99%
See 1 more Smart Citation
“…The belief that he or she can put together a donor network and raise the necessary funds to win will be crucial to a candidate's decision. The political ambition literature tells us that women are less likely to view themselves as qualified to run for office, and they are more likely to express concerns about fundraising (Fox and Lawless 2011;Fulton et al 2006;Jenkins 2007). Thus, more Democratic women than Republican women may run because the Democratic women see more potential avenues for fundraising, which helps them overcome this ambition deficit.…”
Section: Evaluating Gender and Partisan Differences In Fundraising: Amentioning
confidence: 99%
“…Given that the networks of donors that contribute to political campaigns are overwhelmingly male dominated (Burns, Schlozman, and Verba 2001;Francia et al 2003), aspiring female candidates may have more difficulty imagining and assembling a coalition of financial backers. Indeed, surveys regarding political ambition and candidate attitudes indicate that women devote more time and effort to fundraising and that women are more deterred by the costs of a campaign, particularly the need to fundraise (Fulton et al 2006;Jenkins 2007). Beyond the ambitions of individual aspirants, parties consider fundraising a key test of viability.…”
Section: Gender and Campaign Financementioning
confidence: 99%
“…In particular, women candidates face the possibility of sexism in media coverage 39,47,48,49,50,51,52,53 and recruitment, 57,58,172 online harassment, 173 violence, 174 or fundraising, where women have to work much harder to raise similar amounts as men. 11,175 Women may also face problematic voter stereotypes associated with their fertility 176 or lack thereof, 177 or how old their children are. 178 Women and men may also face different economic risks by entering the political arena.…”
Section: Sweet-cushmanmentioning
confidence: 99%
“…In contrast, 21.2% of men had run against incumbents, and 78.8% had run for open seats (The Pennsylvania General Assembly 2015). Women are somewhat less likely than men to challenge an incumbent, perhaps because of a lack of confidence in their qualifications (Fox and Lawless 2010a, 2010b, 2013, even though there is no significant difference in the performance of female and male candidates (Darcy and Schramm 1977;Jenkins 2007;Schlozman and Uhlaner 1986).…”
Section: Running For Open Seatsmentioning
confidence: 99%
“…As early as 1977, Darcy and Schramm found that "candidate sex has little or no effect on election outcomes" (9), and women perform just as well as men when it comes to campaign fund-r aising (Jenkins 2007;Schlozman and Uhlaner 1986). Such results suggest that there is little difference between male and female candidates; instead, the problem is that women are not emerging as candidates to begin with.…”
mentioning
confidence: 99%